A phase II study of combination daunorubicin, cytarabine (Ara‐c), and nilotinib (TAsigna) (DATA) in patients newly diagnosed with acute myeloid leukemia with KIT expression. Issue 3 (22nd January 2023) - Al‐Kali, Aref; Tibes, Raoul; Atherton, Pamela; Palmer, Jeanne; Alkhateeb, Hassan B.; Patnaik, Mrinal; Begna, Kebede; Gangat, Naseema; Hashmi, Shahrukh; He, Rong; Litzow, Mark
Abstract: Acute myeloid leukemia (AML) is a challenging cancer in terms of achieving and maintaining long‐duration remissions. Many novel therapies have been added to the standard regimen (combining cytarabine and anthracycline "7 + 3") to achieve such goals. Nilotinib is an oral multikinase inhibitor that is active against KIT tyrosine kinase, an important stem cell target. In this trial, we combined nilotinib with 7 + 3 induction (daunorubicin 60 mg/m2), high‐dose cytarabine consolidation, and subsequently, if the patient was a candidate, for 2 years' maintenance therapy in patients with AML and KIT (CD117) expression. Patients were allowed to proceed to allogeneic hematopoietic cell transplantation (HCT) if deemed necessary. Our primary goal was increased complete remission rate with this combination. Thirty‐four patients (with a median age 58.5 years) were enrolled on a single‐arm phase II bi‐institutional study; 21 (62%) patients achieved remission. The complete remission rate was 78% in evaluable patients. Thirteen of 34 (38%) patients had allogeneic HCT, all thirteen of which are still alive (100%). Common (>20%) grade 3 non‐hematological toxicities included febrile neutropenia, hypophosphatemia, elevated liver enzymes, and hypertension. Only one patient (3%) died in induction due to liver failure, which was thought secondary to daunorubicin. Our current study reveals good outcomes in patients who received HCT and may warrant a larger study to confirm our findings in that specific population. Abstract : Relapse was uncommon in patients who responded to DATA regimen and had allogenic hematopoietic cell tranplantation (18%).